2009
DOI: 10.1007/s11250-009-9475-8
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with linseed (Linum usitatissimum) cake and/or wheat bran on feed utilization and carcass characteristics of Arsi-Bale sheep

Abstract: Thirty yearling male intact Arsi-Bale sheep with initial body weight (BW) of 15.5 +/- 0.21 kg (mean +/- SD) were used in 90 days feeding trial, 10 days digestibility trial followed by evaluation of carcass parameters at Bokoji, Ethiopia. The objectives were to evaluate effects of supplementation with linseed (Linum usitatissimum) cake (LSC), wheat bran (WB), and their mixtures at 2:1 and 1:2, respectively on feed intake, digestibility, daily BW gain, and carcass parameters. The five treatments included ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
11
5
1
Order By: Relevance
“…The lack of significant difference for non-edible offal's observed in this study is consistent with that noted by others [20]. Conversely, Abebe [25] reported heavier total non-edible offal's for supplemented ArsiBale sheep than the non-supplemented sheep fed basal diet of grass hay.…”
Section: Non-carcass Componentssupporting
confidence: 92%
“…The lack of significant difference for non-edible offal's observed in this study is consistent with that noted by others [20]. Conversely, Abebe [25] reported heavier total non-edible offal's for supplemented ArsiBale sheep than the non-supplemented sheep fed basal diet of grass hay.…”
Section: Non-carcass Componentssupporting
confidence: 92%
“…The ADF content of hay obtained in this study was in an agreement with 468 g/kg DM reported by Abebaw and Solomon (2008), but higher than the value (445 g/kg DM) reported by Tafa et al (2010) and lower than the value (510 g/kg DM) reported by Dessie et al (2010). The ADL content of grass hay used in the current study was comparable to the result obtained by Dessie et al (2010), but higher than 43.6 and 56 g/kg DM reported by Tafa et al (2010) and Bishaw and Melaku (2008), respectively. The diff erence in the ADL content might be due to the diff erence in the proportion of grass species and stage of maturity at the harvest.…”
Section: As Illustrated Insupporting
confidence: 89%
“…The digestibility of DM in WB in this study was 60.2%. Similar result was reported by Tafa et al (2010) when linseed cake and or wheat bran was supplemented to Arsi-Bale sheep fed grass hay. In the current study, the higer apparent digestibility of DM and CP could be attributed to higher protein and lower fi ber content of the supplement diets.…”
Section: As Illustrated Insupporting
confidence: 88%
See 2 more Smart Citations